DASEIN AS DESIGN Or: Must Design Save the World? - Oosterling, Henk (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
Creativity moves from the exclusive domain of the designer intothe space between disciplines and between producer andconsumer. A new form of design is needed, i.e. relational design.Relational design has to focus on relationships and responsibilitiesinstead of a focus on the individual. Relational design gives us thenthe opportunity to go beyond hyperconsumerism andindividualism.